Edge to Edge : Australian Contemporary Art to Japan. - Hara Museum of Contemporary Art, Tokyo; Nagoya City Art Museum, Nagoya; Hokkaido Museum of Modern Art, Sapporo (Osaka : The National Museum of Art, 1988)
Brown-Rrap, Julie ; Dunn, Richard ; Henson, Bill ; Lee, Lindy ; Nixon, John ; Parr, Mike ; Redgate, Jacky ; Tillers, Imants ; Tyndall, Peter ; Unsworth, Ken ; Watson, Jenny
Edge to Edge : Australian Contemporary Art to Japan, The National Museum of Art, Osaka, 28 May - 12 July 1988 ; Hara Museum of Contemporary Art, Tokyo, 10 Sept. - 23 Oct. 1988 ; Nagoya City Art Museum, Nagoya, 11 Feb. - 26 Mar. 1989 ; Hokkaido Museum of Modern Art, Sapporo, 7 Apr. - 29 Apr. 1989
boek
Keywords: Australië